Impact of Political and Terrorist Events on Stock Market Returns: A Case Study in South Asian Context - Mian Sajid Nazir; Muhammad Khalid Khan; Adeel Akram; Ishfaq Ahmed (Journal of Political Studies, 2018)
Efficient Market Hypothesis (EMH) suggests that markets are rational and reflect all information. So, no investor can beat the market by generating abnormal returns. But it is found that stock markets deviate (anomalies) and contradicts the rule of EMH. To investigate this issue in this event study political and terrorist events are considered as the external information. Political and terrorist events create uncertainty and risk for the investors in the capital markets. These events have been increasing dramatically in the last decade by which investors face hesitation and fear while investing in a politically unstable and unsafe country. The stock markets in our study include Pakistan Stock Exchange (Pakistan), Bombay Stock Exchange (India), Chittagong Stock Exchange (Bangladesh) and Colombo Stock Exchange (Sri Lanka). This comparative study is the effort to find the answer of whether political and terrorist events have any impact on the Stock Market returns on the financial markets of South Asian countries. Event study methodology is used in the study. By using Market Model, we analyzed 47 terrorists and 45 political events in all four countries of our study during 2005-2016. The empirical result shows that the political and terrorist events have significant impact on stock market returns. Moreover, the results show that the stock markets of South Asian countries are inefficient on 15-day event window. While the results on 2nd day event windows are insignificant. The noisy information does not absorb by the markets shows the contradiction to the assumptions of efficient market hypothesis (EMH).